BIOTECHNOLOGICAL APPROACHES TO ENHANCING THE PHYSICAL AND PSYCHOLOGICAL CAPABILITIES OF MILITARY PERSONNEL - Gaipov Ravshan Abdujalilovich (The Conference Hub, 2025)
This article analyzes the role of modern biotechnological approaches in enhancing the physical and psychological capabilities of military personnel. As a result of scientific progress, various technologies have been developed that increase human endurance, resistance to stress, and cognitive performance. In particular, the prospects for enhancing military potential through gene therapy, biochips, neurostimulation methods, rational nutrition, and adaptogenic agents are examined.
Keywords: Biotechnology, military psychology, gene therapy, biochip, neurostimulation, stress resistance.